AN ANALYSIS OF STUDENTS’ MOTIVATION IN E-LEARNING - Datu, Resi; Tuerah, Ignatius J.; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aimed to describe the students’ motivation toward E-learning and conducted at English Education Department of Universitas Negeri Manado with the used of quantitative descriptive research design. The instrument to collect the data was a questionnaire that consist of 20 statements with 4 different scales to measure the respondents’ answers. The sample was taken using the simple random sampling from the total 169 population of the 7th semester students who spent most of their learning activity in college through online class. The total number of students who responded to the questionnaire via Google Form that had been given was 25 students. After all the data has been collected, it was analyzed using the percentage formula and the results were described in every number using diagram. The final result of this study showed that most of the students had positive reaction or responses about using E-learning, but there were also several important things that could affect and decrease the students’ motivation. Based on the findings, it could be concluded that the students had good motivation in learning English using E-learning, but some things need to be considered and overcome when conducting this method of learning.